2003
DOI: 10.3109/13814780309160410
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, attitudes and behaviour regarding antibiotics

Abstract: Antibiotic resistance is a matter of concern for the public. Mixed opinions about the use of antibiotics for common respiratory tract infections were heard. Encouragingly the majority of people suffering an RTI during the review period treated themselves with paracetamol-based products for symptom relief. Those who consulted a doctor were in the minority but were likely to be prescribed antibiotics. Future local health education initiatives should target antibiotic use for sore throats as well as colds and 'fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 12 publications
1
39
0
1
Order By: Relevance
“…Lindberg and colleagues found that the 13 patients they interviewed related resistance to the bacterium, which is not so surprising given that the term itself declares the Staphylococcus resistant, and that this organism is also commonly known as a 'super-bug'. 37 Nevertheless, most surveys about the public perception of antibiotic resistance have been naïve to the possibility of multiple interpretations of the term antibiotic resistance', [11][12][13][14][15] and did not give respondents the opportunity to elaborate on the issue. [13][14][15] Respondents to those surveys may not have interpreted antibiotic resistance as intended by the researchers.…”
Section: Results In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Lindberg and colleagues found that the 13 patients they interviewed related resistance to the bacterium, which is not so surprising given that the term itself declares the Staphylococcus resistant, and that this organism is also commonly known as a 'super-bug'. 37 Nevertheless, most surveys about the public perception of antibiotic resistance have been naïve to the possibility of multiple interpretations of the term antibiotic resistance', [11][12][13][14][15] and did not give respondents the opportunity to elaborate on the issue. [13][14][15] Respondents to those surveys may not have interpreted antibiotic resistance as intended by the researchers.…”
Section: Results In Contextmentioning
confidence: 99%
“…11,12 For example, surveys examining patients' attitudes have used fixed questions with little or no opportunity for follow-up of patients' views or understanding. [13][14][15][16] Few studies have explored patients' understanding of antibiotic resistance as a term used in healthcare discourse. Although two recent qualitative studies have explored patient and public attitudes towards antibiotic resistance, they were limited to the United Kingdom, and the wider implications were not considered in depth.…”
Section: Introductionmentioning
confidence: 99%
“…against the level of knowledge on responsive behaviour on antibiotic usage (16,18,20). Our study showed that responsive behaviour and high level of knowledge towards antibiotics less likely to adopt antibiotic resistance as to non-responsive low-level of knowledge (RR 0.76, 95% 0.10 -1.10), while irresponsible attitude towards antibiotics use and altered perception towards antibiotic course completion responds were five (5) times more likely to develop antibiotic resistance as per irrational use of antibiotics as to responsible attitude respondents (RR 5.12, CI 95% 3.37 -7.89) (15,17,27).…”
Section: Discussionmentioning
confidence: 99%
“…Detail findings were presented in (17,27). Similarly our estimations reflect that low level of knowledge with irresponsive behavior three (3) times more likely to evolve least Health assurance calculation (like chronic medical conditions, smoking, alcohol etc) and thus with such perimeters responds were two (2) times at risk of irrational use (RR 2.21, 95% 1.40 -2.79); regardless to the matter of fact either non-compliance or knowledge induced behaviour change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation